Abnormalities of resting-state EEG in patients with prodromal and overt dementia with Lewy bodies: Relation to clinical symptoms - Pascarelli, Maria Teresa; Del Percio, Claudio; De Pandis, Maria Francesca; Ferri, Raffaele; Lizio, Roberta; Noce, Giuseppe; Lopez, Susanna; Rizzo, Marco; Soricelli, Andrea; Nobili, Flavio; Arnaldi, Dario; Fama, Francesco; et al. (Elsevier Ireland Ltd, 2020)
Objective: Here we tested if cortical sources of resting state electroencephalographic (rsEEG) rhythms may differ in sub-groups of patients with prodromal and overt dementia with Lewy bodies (DLB) as a function of relevant clinical symptoms.Methods: We extracted clinical, demographic and rsEEG datasets in matched DLB patients (N = 60) and control Alzheimer's disease (AD, N = 60) and healthy elderly (Nold, N = 60) seniors from our international database. The eLORETA freeware was used to estimate cortical rsEEG sources.Results: As compared to the Nold group, the DLB and AD groups generally exhibited greater spatially distributed delta source activities (DLB > AD) and lower alpha source activities posteriorly (AD > DLB). As compared to the DLB ``controls", the DLB patients with (1) rapid eye movement (REM) sleep behavior disorders showed lower central alpha source activities (p < 0.005); (2) greater cognitive deficits exhibited higher parietal and central theta source activities as well as higher central, parietal, and occipital alpha source activities (p < 0.01); (3) visual hallucinations pointed to greater parietal delta source activities (p < 0.005).Conclusions: Relevant clinical features were associated with abnormalities in spatial and frequency features of rsEEG source activities in DLB patients.Significance: Those features may be used as neurophysiological surrogate endpoints of clinical symptoms in DLB patients in future cross-validation prospective studies.
Keywords: Prodromal and Overt Dementia With Lewy Bodies (DLB); Mild Cognitive Impairment (MCI); Resting State Electroencephalographic (EEG) Rhythms; Exact Low-Resolution Brain Electromagnetic Source Tomography (Eloreta); Visual Hallucinations; Rapid Eye Movement Sleep Behavior Disorders (RBD)